Muktagacha: a targeted nutrition project in Bangladesh - Chowdhury, A Mushtaque R.; Mahmud, Zeba; Chowdhury, Sadia A; Nasser, Kawshiki; Hyder, SM Ziauddin (BRAC Research and Evaluation Division (RED), 2020)
Malnutrition is one of the major public health problems in Bangladesh. Since 1993, BRAC, a national non-governmental organisation (NGO), has been carrying out a targeted nutrition project in a thana (sub-district) of Bangladesh. The major emphasis of the project are nutrition education and food supplementation to the vulnerable groups. This case study, done at the request of UN Food and Agriculture Organisation (FAO), presents the project with special attention given to different aspects of 'targeting'.